PENGARUH PROFITABLITAS, UKURAN PERUSAHAAN, LEVERAGE, DAN PRAKTIK MEKANISME GCG TERHADAP NILAI PERUSAHAAN PADA SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BEI PERIODE 2011-2015 - WAHYUNINGSIH, SRI (Jurnal Ilmu Manajemen (JIM), 2019)
The purpose of this study is to understand the effect of profitability, company size, leverage and good corporate governance mechanisms on firm value. The object of this research is mining sector companies on the IDX for the period 2011-2015. This study uses a quantitative approach with secondary data. The population in this study consisted of 41 companies, the sample consisted of 27 companies taken according to the sample selection criteria using purposive sampling. The method of data analysis in this study is a multiple regression model. The results of this study indicate that the variable profitability and company size do not affect the value of the company. While leverage and good corporate governance mechanisms have a significant influence on firm value, this shows that the greater the proportion of capital using long-term debt in corporate funding the greater the risk of the inability to pay long-term debt and interest at maturity and will have an impact on campus performance in operating the company so that it will affect the profit and value of the company. Keywords: Leverage, good corporate governance mechanism, company value, profitability, company size